2001
DOI: 10.1081/amp-100104304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Austempering Temperature on Fracture Toughness of a Low Manganese Austempered Ductile Iron (Adi)

Abstract: The influence of microstructure on the plane strain fracture toughness of an unalloyed, austempered ductile cast iron (ADI) with low manganese content (Ͻ0.15 wt %) and with predominantly as-cast (solidified) ferritic structure was studied. Test specimens were austenitized at 927°C (1700°F ) for 2 hr and then austempered over a range of temperatures to produce different microstructures. The microstructures were characterized through optical microscopy and X-ray diffraction. Plane strain fracture toughness of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…These results are consistent with the published literature ( Ref 3,4,8,[15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Heat Treatments and Microstructuressupporting
confidence: 96%
“…These results are consistent with the published literature ( Ref 3,4,8,[15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Heat Treatments and Microstructuressupporting
confidence: 96%
“…The obtained microstructure consisting of ausferritic ferrite free of carbide and stable, reacted, highly enriched retained austenite, attained the best combination of mechanical properties. (6) It has been demonstrated that the prolonged austempering time (beyond the time at which the Stage II reaction starts) results in a transformation of the stable, reacted, highly enriched retained austenite to bainite (ferrite and carbides).…”
Section: Discussionmentioning
confidence: 99%
“…A further contribution in the field of optimization of heat treatment parameters was given by Putatunda [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of ADI focused upon the effects of austempering treatments Ausferrite obtained using higher austempering temperatures bear coarse upper bainitic ferrite adjacent to plenty of retained austenite This structure exhibits lower hardness, strength, and higher ductility. Conversely, needle‐like lower bainitic ferrite is formed at lower austempering temperature leading to higher hardness, strength, and reduced ductility.…”
Section: Introductionmentioning
confidence: 99%